Legitimization of pension institutions. Need or necessity? - Marzec, Małgorzata; Szczudlińska-Kanoś, Agnieszka (Legitymizacja systemu emerytalnego. Potrzeba czy konieczność?, 2019)
The pension system in its functioning and activity should be legitimized as an actual condition in performing specific tasks in accordance with the general requirements and expectations attributed to the pension system. In the case of institutions of the pension system, legitimacy should concern both the organization of the system itself ensuring the implementation of basic tasks, e.g. ensuring system security, guaranteeing the solvency of certain benefits, etc., as well as organizations at the level of individual institutions (public and private). The aim of the article is to analyze the issue of legitimizing the pension system from the point of view of institutions operating in the pension system. The article is teoretical and presents a model enabling understanding of the significant problem of legitimization against the background of functioning pension institutions. The study presents the adaptation of the conceptual (semantic) apparatus to the analysis of the legitimacy of the pension system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 172-184
Keywords: legitimization; pension system; social responsibility; legitymizacja; system emerytalny; społeczna odpowiedzialność